Բնակլիմայական պայմանների ազդեցությունը հավերի էյմերիոզի տարածվածության վրա ՀՀ Արմավիրի և Արարատի մարզերում - Հակոբյան, Ա. Ռ.; Գրիգորյան, Վ. Վ.; Երիբեկյան, Ս. Վ.; Գրիգորյան, Լ. Հ. (ՀԱԱՀ հիմնադրամ)
Հետազոտություններն իրականացվել են ՀՀ Արմավիրի և Արարատի մարզերի թռչնաբուծական տնտեսություններում։ Հայտնաբերվել է էյմերիաների երկու տեսակ՝ Eimeria acervulina և Eimeria tenella։ Ինվազիայի առավել բարձր էքստենսիվություն և ինտենսիվություն գրանցվել են գարնանը, իսկ առավել ցածր՝ ձմռանը։ Հետազոտված թռչնաբուծական տնտեսություններում հավերի էյմերիոզի ցածր էքստենսիվությունն ու ինտենսիվությունը պայմանավորված են Արմավիրի և Արարատի մարզերի աշխարհագրական դիրքով ու կլիմայական առանձնահատկություններով։ Исследования проводились в птицеводческих хозяйствах Армавирской и Араратской областей РА. Были обнаружены два вида эймерий – Eimeria acervulina и Eimeria tenella. Наиболее высокая экстенсивность и интенсивность инвазии были отмечены весной, а наиболее низкие показатели – зимой. Низкая экстенсивность и интенсивность эймериоза кур в исследованных птицеводческих хозяйствах обусловлена географическим положением и климатическими особенностями Армавирской и Араратской областей. One of the current issues of small poultry farms is the prevalence of Eimeriosis infection (especially in floor housing conditions). The research activities were conducted throughout 2021-2022 years in the small rural poultry farms of some communities at the RA Armavir and Ararat marzes. Eimeria infection of chickens was identified on the basis of the results of laboratory tests performed throughout the year. Two species of Eimeria were detected: Eimeria acervulina and Eimeria tenella. Infected samples made up 36% of the overall examined ones. Heat and humidity are among the factors of external environment contributing to the Eimeria propagation. During the year, one or two outbreaks of epidemic nature of invasion may be recorded. The intensity of invasion in Armavir and Ararat marzes was 33 % and 39 %, respectively. Weather conditions favor the preservation and sporulation of Eimeria oocysts in the outdoor environment, leading to spring outbreaks of infection. During the research, as a result of the monitoring carried out in the permanently insecure areas against the disease, high indicators of the extensity and intensity of the invasion were recorded from the beginning of April until the first ten days of June. Lack of precipitation in the summer contributed to a sharp decline in the extensity and intensity of the invasion. And in the long and warm autumn, due to heat and humidity, a certain increase in the mentioned indices was registered, which, anyhow, did not lead to autumn outbreaks of the invasion.
Keywords: Անասնաբուժական բժշկագիտություն և անասնաբուծություն